Digitalization in urban planning: new digital technologies for sustainable cities - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmers and tools section presents presents the different strategies and tools that guide the digitalization of urban planning. This paper explores digitalization in urban transformation, with a specific focus on sustainability and how digital technologies act as catalysts for the achievement of environmental, social and economic sustainability goals. Concrete examples are presented of strategies and plans implemented by some cities, New York, Amsterdam and Turin, that have successfully integrated digital to address complex challenges such as climate change, resource management and citizen well-being, demonstrating the potential of digitalization to influence urban governance.